2002
DOI: 10.1002/cncr.10321
|View full text |Cite
|
Sign up to set email alerts
|

Cancer trends among Hispanic men in South Florida, 1981–1998

Abstract: Schlimmer Finger: Proteinbeschichtete magnetische Partikel mit farbstoffmarkierten Fragmenten (siehe Bild) sind Konjugate aus Antikörpern und magnetischen Partikeln, die Drogen und deren Metabolite, z. B. Methadon und Benzoylecgonin, in Fingerabdrücken nachweisen können. Die Konjugate machen den Fingerabdruck sichtbar, sodass der Nachweis von Drogenmissbrauch und die Identifizierung der Person in einem Schritt möglich werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, once acculturated after living within the U.S. for extended periods, rates for the four most common malignancies begin to increase among these groups. 1012 However, it should be noted that although overall incidence of cancer in American Indian/Alaska Native is lower than non-Hispanic whites, when incidence rates are examined geographically, there are significant differences in incidence between American Indians/Alaska natives and non-Hispanic whites especially in the Northern Plains and Alaska. 13,14 As mentioned earlier, race and ethnic heritage are not the only factors that influence cancer incidence.…”
Section: Cancer Health Disparitiesmentioning
confidence: 99%
“…However, once acculturated after living within the U.S. for extended periods, rates for the four most common malignancies begin to increase among these groups. 1012 However, it should be noted that although overall incidence of cancer in American Indian/Alaska Native is lower than non-Hispanic whites, when incidence rates are examined geographically, there are significant differences in incidence between American Indians/Alaska natives and non-Hispanic whites especially in the Northern Plains and Alaska. 13,14 As mentioned earlier, race and ethnic heritage are not the only factors that influence cancer incidence.…”
Section: Cancer Health Disparitiesmentioning
confidence: 99%
“…Puerto Ricans were more acculturated than Dominicans, and a greater proportion of Puerto Ricans compared to Dominicans were born in the U.S or emigrated ≤ 18 years of age. Among Latinos, acculturation and increased duration of U.S. residence are theorized to be related to worse CRC outcomes due to the adoption of poor health behaviors prevalent in the host culture pertaining to diet, physical activity, and alcohol and tobacco use [1, 13-16]. Moreover, the smoking and obesity rates of Puerto Ricans were significantly greater than those of Dominicans, and both smoking and obesity are known risk factors for CRC [3].…”
Section: Discussionmentioning
confidence: 99%
“…The authors propose acculturation of unhealthy behaviors in the U.S., such as cigarette use, as one theory to account for this discrepancy in CRC risk among Puerto Ricans based on country of residence. An earlier study demonstrated the change in cancer incidence rates among Latino and white residents in Florida from 1981-1989 to 1990-1998 [16]. Over time, the age-adjusted CRC incidence rate for Latinos increased (47.9 per 100,000 to 53.2 per 100,000) whereas that for whites decreased (69.9 per 100,000 to 65.6 per 100,000), wherein the risk for CRC among Latinos gradually approached the risk of CRC among whites in the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation